The Syntax of Experiencers in Sereer-Siin - Tamba, Khady (My University, 2019)
The special grammatical status of experiencers has been at the center of various studies within linguistics for several decades (Belletti & Rizzi 1988; Ameka 1990; Pesetsky 1995). This attention is due to the fact that there are specific syntactic features that are only associated with experiencers (Landau 2010). This study investigates object experiencers in Sereer-Siin – a dialect of Sereer, a West Atlantic language of the Niger Congo family spoken in Senegal. I show that object experiencers in Sereer can be classified in two groups according to their syntactic behavior. In this study I provide evidence that Sereer experiencers can be used to extend Belletti and Rizzi’s traditional classification of experiencers. Using data from Italian, Belletti and Rizzi have classified object experiencers in two groups. The first one they refer to as class II, has a nominative theme and an accusative experiencer whereas the second one, class III, has a nominative theme and a dative experiencer. In Sereer, like in Italian, different properties of object experiencers account for asymmetries noted with respect to constructions like passive, antipassive and nominalization.
Keywords: Sereer-Siin; linguistics; Syntax of experiencers